When suppliers shift my boundaries: Supplier employee mobility and its impact on buyer firms' sourcing strategy - Chondrakis, George; Sako, Mari (Strategic Management Journal, 2020)
Research summary Buyer firms respond to supplier employee mobility by reshuffling work among suppliers. However, the extant literature has not considered plural‐sourcing firms which can bring work back in‐house. In this paper, we develop a governance framework in which buyers engage in a comparative assessment of the costs associated with different sourcing modes following supplier employee mobility. Due to the imperfect transferability of social capital and associated uncertainty, buyers face increased contracting costs when supplier employees move. This prompts plural‐sourcing buyers to increase their reliance on insourcing when the costs of adjusting in‐house capacity are relatively low and when the costs of switching to alternative suppliers are relatively high. The analysis of data on patent prosecution activities and patent attorney mobility provides support to our theory. Managerial summary This study provides a decision framework for buyer firms when their suppliers experience employee departures. Buyers may choose to (a) stay with the suppliers suffering employee losses or (b) follow mobile employees to their new suppliers. However, in both cases contracting becomes more difficult due to the disruption in supplier relationships or the need to work with new suppliers. There is a third option (c) though which is to bring work in‐house. We explain that buyers opt for option (c) when it is easy to expand in‐house capacity and when the costs of switching to alternative suppliers already in use are relatively high. Thus, supplier employee mobility may lead buyer firms to adjust their reliance on outsourcing even when there are no buyer employee departures.